Implementation of the Team Quiz Learning Method as a Learning Medium in Schools in Islamic Religious Education (PAI) - Camila Mulia Ramadhani; Iqbal Amar Muzaki; Afiyatun Kholifah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Education plays a crucial role in shaping a generation that excels not only intellectually but also possesses noble character. One of its main components is Islamic Religious Education (PAI), which focuses on instilling Islamic values ​​in students' daily lives. However, Islamic Religious Education (PAI) learning practices in the field often rely on traditional methods such as lectures and memorization, which lack active student engagement. To address this issue, innovative approaches are needed, one of which is the Team Quiz method. This approach combines group work and quizzes in a competitive yet fun atmosphere, thereby increasing student engagement. Based on literature studies from various sources, Team Quiz is effective in deepening understanding of the material and developing social skills such as cooperation, communication, and responsibility. In the context of Islamic Religious Education, this method helps convey Islamic values ​​in a more applicable and meaningful way. Furthermore, it supports strengthening learning motivation, reducing academic gaps, and strengthening student character. The implementation of Team Quiz also aligns with the demands of 21st-century skills and the principles of the Independent Curriculum, which centers on differentiation and student participation. Teachers act as active facilitators in guiding students to learn independently and collaboratively.